Clinical study - Pratt, Gilberto (Cirugía del Uruguay, 1971)
The clinical symptoms of pulmonary embolism vary greatly. Susceptibility is considered and a brief analysis is made of the clinical picture determined by massive pulmonary embolism, recent multiple embolism and pulmonary infarction. The examinations which are complementary to diagnosis are listed with special emphasis on simple radiography, ECG, enzymological studies and ventilation-irrigation disorders.